Reasons Justifying Criminal Abolition in the Indonesian Legal System - Erwin Asmadi (International Journal Reglement & Society (IJRS), 2022)
In criminal law, there are several reasons that can be used as a basis for judges not to impose penalties/criminals on perpetrators or defendants who are brought to court because they have committed a crime. These reasons are called the reasons for the abolition of the crime. This research was conducted using a normative legal research method that uses secondary data sources in the form of legal materials which are researched through library research. Based on the results of the study, it is known that the reason for the abolition of the crime is a regulation that is primarily addressed to judges. This regulation stipulates under what circumstances an offender, who has fulfilled the formulation of the offense that should have been sentenced, is not sentenced. The judge places the authority of the legislator to determine whether there have been special circumstances as formulated in the reason for the abolition of the crime. The division of forgiving reasons and separate justifying reasons into forgiving reasons includes the inability to be responsible, forced defense that exceeds the limit, carrying out an invalid position order in good faith; justifications include coercive power or overmacht, forced defense, carrying out the provisions of the law, and carrying out office orders from superiors